DESIGNING THE HUMAN RESOURCE SCORECARD AS A PERFORMANCE MEASUREMENT OF HUMAN RESOURCE - Muslim, Erlinda; Firania, Frinda (SBM ITB, 2016)
Abstract. This study discusses the importance of performance measurement in a company because it can be used to assess the success of the company. The purpose of this study is to design and measure the performance of a MIGAS company using the Human Resource Scorecard approach by establishing the priority weight of strategic objectives and Key Performance Indicators on the Strategy Map through the Analytical Network Process. Results of this study are acquiring 16 strategic objectives, and 20 leading indicators and 17 lagging indicators. Results of the priority weight show that the company is more focused on the operational perspective, then the financial perspective, strategic perspective, and the last is the customer perspective. From the design and measurement results obtained from this study, a plan of the Human Resource Scorecard design was created that can be used by the company.Keywords: performance measurement, human resource scorecard, strategy map, key performance indicator, analytical network processAbstrak. Penelitian ini membahas mengenai pengukuran kiner ja yang merupakan salah satu faktor sangat penting bagi perusahaan karena dapat dipergunakan untuk menilai keberhasilan perusahaan. Tujuan penelitian ini adalah merancang dan mengukur kinerja sumber daya manusia salah satu perusahaan MIGAS melalui penetapan prioritas sasaran strategis beserta Key Performance Indicator (KPI) pada Peta Strategi melalui metode Analytical Network Process. Hasil penelitian ini diperoleh 16 sasaran strategis, dan terdapat 20 leading indicator dan 17 lag ging indicator. Hasil pembobotan prioritas menunjukkan bahwa perusahaan lebih memfokuskan kepada perspektif operasional, baru kemudian perspektif finansial, perspektif strategis, dan terakhir adalah perspektif pelanggan. Dari hasil perancangan dan pengukuran ini diperoleh perencanaan perancangan Human Resource Scorecard yang dapat digunakan oleh perusahaan.Kata kunci: pengukuran kiner ja, human resource scorecard, peta strategi, key performance indicator, analytical networkprocess